Enhancing the growth, yield and physiological response of two lettuce (Lactuca sativa L.) cultivars through NFT system optimization - Pastor-Arbulú, Paulo; Rodríguez-Delfín, Alfredo (Frontiers in Plant Science, 2025)
IntroductionIn the context of increasing pressure on agricultural resources, hydroponic systems such as the nutrient film technique (NFT) are gaining prominence for their ability to optimize water use and space efficiency, and crop productivity in controlled environments. Lettuce (Lactuca sativa L.), a high-value leafy vegetable, is a key cash crop in controlled-environment agriculture. Light quality and intensity -critical drivers of plant physiology- require constant monitoring in soilless systems to ensure consistent performance. However, the interaction effects of NFT system design and cultivar selection on physiological behavior and yield stability remain underexplored.MethodsThis study evaluated the growth, yield, and physiological responses of two lettuce cultivars, Tropicana and Starfighter, cultivated in three NFT configurations: module I (8-channel) with a horizontal layout; and module II (13-channel) and module III (10-channel), both with pyramidal layouts. Although all the treatments were exposed to similar microenvironmental conditions, the photosynthetic photon flux density (PPFD) was monitored throughout the crop cycle to maintain light uniformity. Agronomic performance was evaluated through biometric parameters in roots, stems, leaves and heads, and the yield was calculated per unit area; while the physiological responses included measurements of relative and total chlorophyll content and nitrate reductase enzymatic activity.Results and discussionTropicana generally outperformed Starfighter, particularly in modules II and III, which also supported higher pigment accumulation and improved nitrogen metabolism across both cultivars. The highest yields were achieved by Tropicana in modules II (14.14 kg·m-2) and III (13.96 kg·m-2), closely followed by Starfighter in module II (13.45 kg·m-2). These findings highlight how strategic integration of system configuration and cultivar selection can increase physiological efficiency, stabilize yields, and promote sustainability in hydroponic lettuce production.